Multi-mode enhanced Raman scattering spectroscopy using aggregation-free hybrid metal/metal-oxide nanoparticles with intrinsic oxygen vacancies. Issue 9 (22nd February 2023) - Davison, Gemma; Yin, Yidan; Jones, Tabitha; Parkin, Ivan P.; Peveler, William J.; Lee, Tung-Chun
Abstract : Un-aggregated plasmonic nanoparticles with a metal oxide coating display persistent enhanced Raman spectra in solution. Enhancement can be further boosted with UV-irradiation (PIERS) to detect nanomolar concentrations of explosive dinitrotoluene. Abstract : Surface-enhanced Raman scattering (SERS) spectroscopy, with strong and stable signals, was achieved in aqueous solution using colloidal hybrid nanoparticles, consisting of gold nanotriangles (Au NTs) with a nanoscale coating of tin dioxide (SnO2 ). The observed strong SERS signals can be attributed to an electromagnetic enhancement from the anisotropic Au NTs, and chemical enhancement resulted from the photo-induced charge transfer from SnO2 to Au NTs. The latter was enabled by the presence of persistent inter-band levels introduced by the intrinsic oxygen vacancies in SnO2, as well as by the nanoscale mixing of the two components. Moreover, the intrinsic oxygen vacancies in highly defected SnO2 nanostructures and the aggregation-free approach underpin the high stability of SERS signals. The multi-mode enhanced Raman signal could be further boosted by in situ UV-irradiation and, as a proof-of-concept application, detection of an explosive marker 2, 4-dinitrotoluene (DNT) was demonstrated in aqueous solution, achieving a detection limit down to 6 nM (1 μg mL −1 ) with a significant signal enhancement of 22 times over and above the SERS signals of bare Au NTs.